2010
DOI: 10.1039/b914016f
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the application of vibrational spectroscopy to the determination of the structures of NO adsorbed on single-crystal metal surfaces

Abstract: Recently derived vibrational spectroscopic data from NO ligands in metal coordination or cluster compounds, corrected to 'neutral coligand' status, are used to help identify the structures of related surface species from NO chemisorbed on metal single-crystal surfaces at low coverage. The derived conclusions form the basis for a systematic review of the structural information derivable from the extensive vibrational spectroscopic literature in this area, considered in relation to information from other physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…This interaction, which is electrostatic, is enhanced if NO is negatively charged via electron transfer from the surface (back-donation). We confirmed back-donation using EELS by observing the ν N–O peaks for water–NO complexes with reduced energies (Figure ); back-donation to the half-filled antibonding 2π* orbital of NO decreases the ν N–O energies. , Hence, we propose that surface-enhanced electrostatic interaction exists between NO and water molecules. This electrostatic interaction between surface-bound NO and water was nominally called “H-bond” interaction, and a similar mechanism has been previously proposed to rationalize the attractive interaction between NO and water on Cu(110), NO and NH 3 on Pt(111), , and O 2 and NH 3 on Pt(111). , Typical H-bond interaction involves O–H or N–H groups, where the H-atom of the polar group is donated to the nonbonding orbital (lone pair electrons) of another group. , The main mechanism involved in the formation of a H-bond is polarization of the nonbonding orbital induced by the donated polar group and partial electron transfer of the lone pair electrons (overlap of the orbitals) between the molecules.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…This interaction, which is electrostatic, is enhanced if NO is negatively charged via electron transfer from the surface (back-donation). We confirmed back-donation using EELS by observing the ν N–O peaks for water–NO complexes with reduced energies (Figure ); back-donation to the half-filled antibonding 2π* orbital of NO decreases the ν N–O energies. , Hence, we propose that surface-enhanced electrostatic interaction exists between NO and water molecules. This electrostatic interaction between surface-bound NO and water was nominally called “H-bond” interaction, and a similar mechanism has been previously proposed to rationalize the attractive interaction between NO and water on Cu(110), NO and NH 3 on Pt(111), , and O 2 and NH 3 on Pt(111). , Typical H-bond interaction involves O–H or N–H groups, where the H-atom of the polar group is donated to the nonbonding orbital (lone pair electrons) of another group. , The main mechanism involved in the formation of a H-bond is polarization of the nonbonding orbital induced by the donated polar group and partial electron transfer of the lone pair electrons (overlap of the orbitals) between the molecules.…”
Section: Resultssupporting
confidence: 56%
“…Adsorption and molecular interaction are well-defined for individual molecules. Water prefers island nucleation to monolayer wetting on Cu(111) owing to the dominance of water–water interaction over water–surface interaction, i.e., the hydrophobic nature of the surface. ,, This preference was confirmed by scanning tunneling microscopy (STM) observations that allowed direct imaging of individual ice clusters nucleated on the surface. , The adsorption of NO on Cu(111) has been studied by using various surface-sensitive spectroscopies, with monomeric adsorption reported to dominate at low coverage on Cu(111). However, a recent study using STM revealed that NO prefers characteristic trimer formation, even at very low coverage, arising from covalent interaction between NO molecules possessing an unpaired 2π* electron . Trimer formation was also verified by vibrational analysis using electron energy loss spectroscopy (EELS) .…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the adsorption and reactivity of nitric oxide (NO) on metal surfaces is essential from fundamental as well as practical application points of view. As an important step for catalytic NO reduction in automotive exhaust gas conversion, NO adsorption on metal surfaces has been extensively studied in the last two decades. Unlike CO adsorption, the NO adsorption on the metal surfaces exhibits a complicated behavior because of its open shell structure of 2π* orbitals. On the metal surfaces, NO undergoes molecular or dissociative adsorption depending on coverage, surface temperature, and the nature of the metals. At low temperature, molecular adsorption of NO mainly takes place where NO adsorbs as a monomer in many different binding geometries, namely upright, side-on, ,, tilted ones; or as a dimer in a high-coverage regime owing to the intermolecular interaction. Furthermore, NO can be dissociated into N and O adatoms at higher temperatures, but whether dissociation occurs strongly depends also on surface coverage. The origin of NO adsorption on metal surfaces is the back-donation process where 2π* orbitals of NO hybridize with the d band of the metal surfaces. …”
Section: Introductionmentioning
confidence: 99%
“…3 Because of the relevance to catalytic reduction of toxic NO x from exhaust gases, the reaction, bonding structure, and valence state of NO on metal surfaces have been studied intensively. [4][5][6] As a result of the presence of an unpaired electron in its 2π * orbital, the bonding structure is complex, and depends on the coverage and temperature as well as on the nature of the surfaces. One of the important characteristics of NO is that it forms a dimer, (NO) 2 , via overlap of an unpaired electron, on metal surfaces as well as in the gas 7 and condensed phases.…”
Section: Introductionmentioning
confidence: 99%